EFEKTIF GOVERNAN DAN PELAKSANAANNYA DALAM PENTADBIRAN ISLAM - Syed Ismail, Sharifah Hayaati (Jurnal Syariah, 2008)
The practice of effective governance has manifested to become crucial in promoting nation building. It is focused on several major entities including politics, economics and administration involving the government, the public and private sectors and also the community. The principles of governance in Islam were undeniably formulated as early as the formation of Madinah as an Islamic state. These can be referred to in the al-Quran and al-Hadith, maqasid al-syari`ah, with the emphasis given on maslahah ‘ammah (public benefits) and the prevention of mafsadah (wrongdoing). This article comprises three major discussions. First is the concept of governance from the perspectives of Islam and the conventional; second is on the uniqueness of al-siyasah alsyar’iyyah as a framework of Islamic effective governance; and finally is the application of effective governance in the era of Islamic rulership. This article found that the notion of effective governance is not new to the Muslim rulership history and practice. Its concept is well defined in the idea of al-siyasah al-syar`iyyah with several terminologies which are more in-depth in their meanings and usages.